Medical writing: A Habit and Discipline We Need to Nurture (Medical Journal of Shree Birendra Hospital, 2016)
Medical writing is an integral part of clinical practice and research. It is needless to say “if you haven’t written and published about it, you haven’t done it in the first place”. Each and every doctor around the world goes through the almost the same training in terms of how rigorous it is and its duration, but still we are unique in our own ways. It is this quality of being unique and innovative that develops the medical field forwards and paves the way for new research.  It is our duty and obligation to share the new knowledge and experience that we have gained during our practice.  The more we share, the more we learn and the more we learn the more we acquire new knowledge for ultimate good of mankind.